Konstruksi Perempuan Dalam Televisi (Pendekatan Ekonomi-Politik) - Syahputra, Iswandi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
In several television programs, women are constructed as representation of reality, not as reflection of reality. Those representations trend to exploit woman sexually. This article describes how women has been constructed in television using political economic media approach. Political economic media studies reveal several economic and political interests behind television programs which involved women.